Analisis Faktor-Faktor yang Mempengaruhi Capital Expenditure - Sharen Criselda, Augustpaosa Nariman (Jurnal Ekonomi, 2021)
This study aims to determine the effect of free cash flow, dividends, interest expense, and firm size on capital expenditures. This study uses a sample of 68 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2019 period. The software used is Eviews version 12 with a purposive sampling method. This study uses a panel of regression data with three models, namely the common effect model, the fixed effect model, and the random effect model. After testing, the random effect model is the chosen model. The results of this study indicate that free cash flow and firm size have a positive and significant effect on capital expenditures. That is, the higher the free cash flow and the larger the size of a company, the higher the amount of capital expenditure. In addition, dividend and interest expenses have a positive and insignificant effect on capital expenditures.